Analisis Perbuatan Mengalihkan dan Merusak Cagar Budaya (Studi Kasus Cagar Budaya Benteng Putri Hijau Di Delitua) - Stepya, Chorry; Ginting, Lilawati (Universitas Ekasakti, 2024)
Protection of cultural heritage in Indonesia is regulated in Law no. 11 of 2010 concerning Cultural Heritage. Violations in the form of destroying cultural heritage can be subject to serious criminal sanctions. One example of a protected cultural heritage is Fort Putri Hijau, with various protection efforts by the government such as restoration, monitoring and outreach, in order to preserve this historic site as the nation's cultural heritage.